Styles of mineralization in the Nautanen IOCG deposit - Edblom, Nils (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2020)
Nautanen is an IOCG (Iron Oxide Copper Gold) deposit located in northern Sweden, 10 km north-east of the town Gällivare in the county of Norrbotten. It was mined for copper for seven years in the early 1900´s and is presently explored by Boliden Mineral AB. The deposit sits within a package of shoshonitic andesites of the Porphyrite group. The rocks have been suggested to be formed in a continental back arc setting and are now hosting the major shear zone NDZ (Nautanen Deformation Zone). The deposit is characterized by an early peripheral magnetite – amphibole alteration and a main mineralization event of pyrite – chalcopyrite – potassium alteration. The majority of the copper- and iron- sulphides occur as veins and stockwork-network textures in strongly potassium-garnet altered schist. The gold occurs as Ag-Au or Ag-Au-Hg mineral grains of 1-30 µm. They are mostly found in fissures within pyrite and magnetite which indicates a later redistribution. The element association and tectonic setting fits well with the general IOCG model, while the mineralogy is not typical for IOCG deposits.